Future foodscapes: Re-imagining agriculture in Latin America and the Caribbean - Morris, Michael; Sebastian, Ashwini; Perego, Viviana Maria Eugenia; Nash, John D.; Díaz-Bonilla, Eugenio; Piñeiro, Valeria; Laborde Debucquet, David; Thomas, Timothy S.; Prabhala, Pradeep; Arias, Joaquin; De Salvo, Carmine Paolo; Centurión, Miriam (World Bank, 2020)
Agriculture and food systems in Latin America and the Caribbean Region (LAC) are rightfully recognized as among the most successful on the planet: they have fed a fast-growing population, facilitated economic development, enabled urbanization, generated substantial exports, and helped drive down global hunger and poverty. Yet despite these significant contributions, the public image of the region’s agriculture and food systems as dynamic, productive, and efficient reflectsonly part of a more complicated reality. The impressive achievements have come at the expense of significant environmental and health costs. LAC agriculture uses over one-third of the region’s land area, consumes nearly three-quarters of the region’s fresh water resources, and generates almost one-half of the region’s greenhouse gas emissions. And despite the consistent food production surpluses, millions of people in LAC regularly go hungry or suffer from malnutrition and related diseases. In short, the region’s successes in feeding the population and exporting food to the rest of the world are exacting high costs on people and on the environment.